Toxicological evaluation of the ketogenic ester bis hexanoyl (R)-1, 3-butanediol: Subchronic toxicity in Sprague Dawley rats. (April 2021) - Stubbs, Brianna J.; Nikiforov, Andrey I.; Rihner, Marisa O.; Weston, Sari L.; Higley, Nancy; Stump, Donald G.; Krane, Gregory A.; Gadupudi, Gopi; Verdin, Eric; Newman, John C.
Abstract: Bis-hexanoyl (R)-1, 3-butanediol (BH-BD) is novel ketone ester undergoing development as a food ingredient to achieve nutritional ketosis in humans. Male and female Crl:CD(SD) rats were administered BH-BD twice daily at 9000, 12, 000 or 15, 000 mg/kg/day, by oral gavage in a 90-day toxicity study with 28-day recovery period; and an interim 28-day phase. Test substance-related early deaths occurred in four females at 15, 000 mg/kg/day. A dose-dependent increase in acute transient postdose (1–3 h) observations of incoordination at ≥12, 000 mg/kg/day and decreased activity at all dose levels were noted in both sexes. Postdose observations were likely associated with peak ketonemia and were considered adverse at 15, 000 mg/kg/day. These daily observations decreased over the study without any persistent effects, as determined during weekly pre-dose observations. Adverse histopathological changes included ulceration/erosion in non-glandular stomach at ≥ 12, 000 mg/k/day and in glandular stomach at 15, 000 mg/kg/day. These histopathological findings were not noted after 28-days of recovery. Due to unlikely human relevance of the rat non-glandular stomach effects for BH-BD and test substance-related mortality at 15, 000 mg/kg/day, the no-observed-adverse-effect level (NOAEL) for subchronic toxicity of BH-BD was determined to be 12, 000 mg/kg/day. Graphical abstract: Image 1 Highlights: We investigated the subchronic toxicity of BH-BD, a novel ketone ester, in rats. Highest dose led to adverse events: mortality, acute behavioral change and forestomach lesions. The no observed adverse effect level of BH-BD was determined to be 12, 000 mg/kg/day.